CONTAMINATIONS IN SUGARCANE JUICE: A TIME EVALUATION - Lisboa, L. A. M.; Pascoaloto, I. M.; Viana, R. da S.; Lopes, P. R. M.; de Figueiredo, P. A. M. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The quality of the sugarcane juice used for ethanol production is essential for the efficiency towards the production of ethanol, with no chemical and biological contaminants that harm and increase the cost of process in the sugar and alcohol sector. Therefore, the aim of this study was to analyze two annual periods of the sugarcane processing in four consecutive years in order to determine the microbiological aspects in the broth within the fermentation vat. Were collected 100 samples from a sugarcane plant, located in São Paulo state, with the following assessment: yeast (active, inactive and total concentration), rods (amount and concentration), shoots; living shoots; viability of yeast and reason of contamination. From the results it was concluded that the sugarcane juice processed and analyzed in such of lower rainfall periods presented higher viability of yeast, less amount of bacteria and, consequently, less contamination rate. Therefore, the high humidity favored the accumulation of waste and increased potential for contamination. In conclusion, the need for adequate crop management minimizes yield losses in the production of ethanol.